2001
DOI: 10.1002/1099-0682(20011)2001:1<223::aid-ejic223>3.0.co;2-u
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Studies of [Os3(CO)10(α-Diimine)]: Structures, Frontier Orbitals and Bonding

Abstract: DFT calculations were performed on Os 3 (CO) 10 (α-diimine) clusters, for α-diimine = DAB (1,4-diaza-1,3-butadiene), PYCA (σ-N,σ-NЈ-pyridine-2-carbaldehyde-imine), and BIPY (2,2Ј-bipyridine). Geometry optimizations were performed for several models of the possible isomers under different conditions. Axial isomers were always found to be the most stable, in agreement with the available X-ray determined structures. A full optimization of the geometry was required in order to improve the quality of the results, b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2002
2002
2005
2005

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 17 publications
(21 citation statements)
references
References 26 publications
2
19
0
Order By: Relevance
“…The four OsÀP bonds (2.477, 2.536, 2.426 and 2.485 ä) are also longer than the corresponding experimental distances of 2.395, 2.441, 2.351, and 2.376 ä, respectively, but the same trends are observed. This difference appears to be a general result of DFT calculations and was also observed for the related complexes [Os 3 (CO) 12 ], [25] [Os 3 (CO) 10 (a-diimine)], [26] and [W(tmbp) 3 ] [11] . In the optimized geometry of [Os 3 -(CO) 10 (bp)], however, the alternation of the CÀC and CC bonds in the biphosphinine rings is well reproduced.…”
Section: Resultssupporting
confidence: 63%
“…The four OsÀP bonds (2.477, 2.536, 2.426 and 2.485 ä) are also longer than the corresponding experimental distances of 2.395, 2.441, 2.351, and 2.376 ä, respectively, but the same trends are observed. This difference appears to be a general result of DFT calculations and was also observed for the related complexes [Os 3 (CO) 12 ], [25] [Os 3 (CO) 10 (a-diimine)], [26] and [W(tmbp) 3 ] [11] . In the optimized geometry of [Os 3 -(CO) 10 (bp)], however, the alternation of the CÀC and CC bonds in the biphosphinine rings is well reproduced.…”
Section: Resultssupporting
confidence: 63%
“…The energy gap was calculated to be 33,792 cm Ϫ1 , which is much greater than that of 1. Contrary to what we have observed here, previous calculations on other [Os 3 (CO) 10 (α-diimine)] clusters [34,35] showed that the HOMOs are mainly metal orbital-based (OsϪOs bonding) while the LUMOs are more localized on the α-diimine ligand. Clearly, the bridging acetylene ligands in the currently studied clusters, significantly affect the orbital structures in the HOMOϪLUMO region.…”
Section: Molecular Orbital Calculationsmentioning
confidence: 99%
“…Based on the contribution of the atomic wavefunctions to the frontier orbitals, the HOMO-LUMO transition has predominant σ(Ru-Os2)-to-π*(α-diimine) character. A comparison of the frontier orbitals with those of [Os 3 (CO) 10 (H-PyCa)] [18] shows that the HOMOs of both clusters are very similar, with only one specific metalmetal(α-diimine) bond involved in the bonding interactions. Notably, the ruthenium centre in 3Ј contributes slightly more (25 %) to the HOMO than the corresponding osmium centre in [Os 3 (CO) 10 (H-PyCa)] (18 %).…”
Section: Density Functional Study Of [Os 2 Ru(co) 10 (Ipr-acpy)] (3)mentioning
confidence: 60%
“…In both model systems, H-PyCa is coordinated with the pyridine ring in the axial position. A recent DFT study of the related cluster [Os 3 (CO) 10 (HPyCa)] [18] has shown that this geometric isomer is more stable than those with the pyridine ring equatorially bound or with both nitrogen atoms coordinated in the equatorial plane.…”
Section: Density Functional Study Of [Os 2 Ru(co) 10 (Ipr-acpy)] (3)mentioning
confidence: 99%
See 1 more Smart Citation